Centrally administered butyrate improves gut barrier function, visceral sensation and septic lethality in rats - Toshikatsu Okumura; Tsukasa Nozu; Masatomo Ishioh; Sho Igarashi; Shima Kumei; Masumi Ohhira (Elsevier, 2021)
Short chain fatty acids readily crosses the gut-blood and blood-brain barrier and acts centrally to influence neuronal signaling. We hypothesized that butyrate, a short-chain fatty acid produced by bacterial fermentation, in the central nervous system may play a role in the regulation of intestinal functions. Colonic permeability and visceral sensation was evaluated in rats. Septic lethality was evaluated in a sepsis model induced by subcutaneous administration of both lipopolysaccharide and colchicine. Intracisternal butyrate dose-dependently improved colonic hyperpermeability and visceral nociception. In contrast, subcutaneous injection of butyrate failed to change it. Intracisternal orexin 1 receptor antagonist or surgical vagotomy blocked the central butyrate-induced improvement of colonic hyperpermeability. The improvement of intestinal hyperpermeability by central butyrate or intracisternal orexin-A was blocked by cannabinoid 1 or 2 receptor antagonist. Intracisternal butyrate significantly improved survival period in septic rats. These results suggest that butyrate acts in the central nervous system to improve gut permeability and visceral nociception through cannabinoid signaling. Endogenous orexin in the brain may mediate the reduction of intestinal hyperpermeability by central butyrate through the vagus nerve. We would suggest that improvement of leaky gut by central butyrate may induce visceral antinociception and protection from septic lethality.